2020
DOI: 10.4414/smw.2020.20394
|View full text |Cite
|
Sign up to set email alerts
|

Active clearance of chest tubes after cardiac surgery: a propensity score matched analysis

Abstract: AIMS OF THE STUDY: Chest tubes inserted to drain shed mediastinal blood after cardiac surgery often become clogged, limiting their capacity to evacuate blood, and leading to blood retention and retained blood syndrome. The aim of this study was the assessment of the efficacy of an active tube clearance (ATC) system in the reduction of retained blood syndrome after cardiac surgery.METHODS: This study included 2461 adult patients undergoing major cardiac surgery. Patients receiving conventional chest tubes only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…There have been 9 clinical trials, including 1 with randomized design, for the device that uses a magnetic actuation system. 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , E1 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been 9 clinical trials, including 1 with randomized design, for the device that uses a magnetic actuation system. 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , E1 …”
Section: Resultsmentioning
confidence: 99%
“…In one, the authors discussed the need for additional training and compliance from the nursing staff to ensure that they were comfortable with chest tube management and used the product per-protocol on a regular basis. 24 This highlights the importance of a systems and protocol-based approach to new techniques and technologies, with training and buy-in from the nursing team, to any active process to prevent chest tube clearance. E2 It further suggests a need for surgeons to continue to engage their ICU colleagues in any process developed to address this problem.…”
Section: Resultsmentioning
confidence: 99%
“…38 Another 2020 study in 471 propensitymatched pairs found that patients with an active clearance tube in the retrosternal position experienced reduced chest tube output compared with conventional chest tubes but showed no significant difference in rates of reexploration for bleeding or tamponade or intervention for pneumothorax or pleural effusion. 39 A couple of studies have suggested that active chest tube clearance has significant benefits. In a propensity-matched analysis in cardiac surgery patients at a single center (302 controls and 337 patients treated prospectively with active clearance), 40 the use of active clearance was associated with fewer drainage procedures for pleural effusions (8.1% vs 22%, P < 0.001) and reduced POAF (25% vs 37%, P = 0.011).…”
Section: Maintenance Of Patencymentioning
confidence: 99%
“…38 Another 2020 study in 471 propensity-matched pairs found that patients with an active clearance tube in the retrosternal position experienced reduced chest tube output compared with conventional chest tubes but showed no significant difference in rates of reexploration for bleeding or tamponade or intervention for pneumothorax or pleural effusion. 39…”
Section: Chest Drain Practicesmentioning
confidence: 99%